2020
DOI: 10.21203/rs.2.20869/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hybrid Strategy of Cervical Artificial Disc and Intervertebral Cage – Biomechanical Effects on the Adjacent Tissues and Implants

Abstract: Background: Adjacent segment degeneration (ASD) is a concern in multi-level ACDF surgery. Hybrid surgery with C-ADR and ACDF are an alternative treatment to reduce the level of increased rigidity, but biomechanical differences between strategies using one C-ADR and two ACDFs have not been thoroughly investigated.Methods: To evaluate the placement-related effects of using one cervical artificial disc replacement (C-ADR) and two anterior cervical discectomy and fusion (ACDF) on tissue responses and implant behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The upper intervertebral space pressure was higher in the flexion/ extension position. Chung et al 5 conducted a biomechanical study and reported that the upper articular surface pressure of the adjacent segment was higher than that of the normal non-surgical group, and the pressure increased by 31.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The upper intervertebral space pressure was higher in the flexion/ extension position. Chung et al 5 conducted a biomechanical study and reported that the upper articular surface pressure of the adjacent segment was higher than that of the normal non-surgical group, and the pressure increased by 31.5%.…”
Section: Discussionmentioning
confidence: 99%
“…C ervical surgery has been widely used in the treatment of cervical trauma, tumors, deformity, and degenerative diseases [1][2][3][4][5][6][7] . The evaluation of cervical spine surgery is based on the medical knowledge of the disease at the time, the developmental status of the internal fixation device, and the technical skill of the surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…16,18 In multilevel ACDF, adjacent discal pressures have been shown to increase by 3-6.7 fold, while CDA either maintains or even decreases adjacent level pressures. [19][20][21][22] In a cadaveric load-control study, Phillips found that a single CDA at C5/6 increased flexion-extension of that motion segment by 4 degrees but did not significantly change rotation or lateral bending. The adjacent segments' motions were unchanged.…”
Section: Biomechanicsmentioning
confidence: 99%
“…Chung et al [5] conducted a biomechanical study and reported that the upper articular surface pressure of the adjacent segment was higher than that of the normal non-surgical group, and the pressure increased by 31.5%.…”
Section: C3/4 Is Prone To Asdismentioning
confidence: 99%